QUANTITATIVE ASSESSMENT OF DEGRADATION CLASSIFICATIONS for DEGRADED ALPINE MEADOWS (HEITUTAN), SANJIANGYUAN, WESTERN CHINA. (12th May 2012) - Li, X.‐L.; Perry, G. L. W.; Brierley, G.; Sun, H.‐Q.; Li, C.‐H.; Lu, G.‐X.
ABSTRACT Improving our understanding of abiotic and biotic thresholds that are transgressed during ecosystem degradation is vital for effective landscape‐level restoration. Establishing logical and consistent typologies of degradation is an important first‐step in this process. Areas of degraded alpine meadow in western China are referred to as Heitutan (or 'black soil beach') and cover vast areas. Previously, four classes of grassland degradation have been differentiated in this large area: non‐degraded alpine meadow and moderate, severe and extreme Heitutan. We evaluated existing field‐based classifications of Heitutan in the Sanjiangyuan region, and examined the criteria on which these classifications are made, by using multivariate statistical approaches. First, we asked whether existing qualitative classifications, based on vegetation cover and the abundance of impalatable plant species, adequately describe the nature of degradation at different locations. We then used a suite of vegetation and soil measures collected across 175 sites spanning a range of degradation conditions to develop a new quantitative assessment of degradation across the alpine meadows of the Qinghai‐Tibetan Plateau. Hierarchical classification highlights two broad classes of degradation: non‐degraded alpine meadow and degraded Heitutan. The non‐degraded category effectively combines the non‐degraded grassland and moderate classes, whereas the degraded Heitutan combines the severe and extreme Heitutan classes. Ordination analyses suggest that the four previously recognized classes of degradation intergrade. Of the 14 biophysical variables used to classify subsites on the basis of their degradation, bare ground area and vegetation cover are the two most useful predictors of grassland condition and associated ecological threshold conditions. Copyright © 2012 John Wiley & Sons, Ltd.